A pilot study on magnitude and reason for encounter of the patients with oral health problems among three different primary care clinics of Kuantan, Malaysia in 2012 - Tin, Myo Han; Md Aris, Mohd Aznan; Tun Ismail, Tuan Sahardi; Thuraiapprah, D. M.; Yusoff, Azizah; Sulong, Robiatu Adawiah (2013)

(untitled)
Aim of the study was to assess the magnitude and reason for encounter (RFE) of the patients with oral health problems (OHPs) among 3 different primary care clinics. Methods: A uniform structured format and open-ended questions were used to collect data from the patients with OHPs who attended at primary care clinic of International, Islamic University, Balok public clinic and private polyclinic Ar Razi in Kuantan, Malaysia between 1st April and 31st July 2012. A cross analysis was done between types of clinic and magnitude of the OHPs.Results: Minimal and maximum number of OHPs per 1000 patients per month in the University clinic, the Balok government clinic and the private poly clinic were 9.36 to 17.9, 10.81 to 25.7 and 4.2 to 14.8 respectively. Night call OHPs cases were only seen at the private poly clinic. The most OHPs were toothache and mouth pain (38%), mouth ulcer (30%), gingivitis (15.6 %), and co-morbidity with medical diseases (4%) respectively. Reasons for consulting OHPs at primary care clinics were non-specific answers same as RFE (56%), easily accessible to services (17%), familiar with general practitioners/family physicians (6.5%), getting emergency treatment for pain release (5%) and co-morbidity with medical diseases (1.3%). Conclusion: This study highlighted that OHPs is one of the RFEs in primary care clinic and need proper training for primary care physicians to provide quality services particularly for common and emergency OHPs in coordinating with oral health practitioners.